584 Characterisation of Global Gastric Cancer Surgery Epidemiology: An International Prospective Cohort Study. (19th August 2022) - Riad, A; Knight, S; Skipworth, R; Griffiths, E; Griffin, M; Harrison, E
Abstract: Aim: We aimed to characterise the global surgical gastric cancer population and variability in disease presentation across different resource settings. Method: GlobalSurg3 was a multicentre, international prospective cohort study of patients undergoing surgery for cancer. Primary outcomes were death or major complications (Clavien-Dindo III/IV) within 30 days of surgery. Income levels were defined using the World Bank classification. Patient characteristics, presentation and disease factors were analysed across income levels. Multilevel logistic regression models were used to explore the effect of patient factors on outcomes. Results: This analysis included 1337 patients from 263 hospitals (high income countries (HICs) N = 712, upper middle income countries N = 289, low and lower middle-income countries (LMICs) N = 336). Most patients presented with gastric adenocarcinoma (81.4%, N=1088) in the distal third of the stomach (43.2%, N=578). Patients undergoing surgery were on average 10 years younger in LMICs compared to HICs (55.4 vs 67.4), and proportion presenting with >10% weight loss was double (64.3%, N=216 vs 30.8%, N=219). Patients in LMICs were twice as likely to require emergency surgery (10.7%, N=36 vs 4.2%, N=30), as did those operated on with palliative intent (21.1%, N=71 vs 11.1%, N=79). Having an increased Eastern Cooperative Oncology Group performance status (ECOG) was associated with significantly increased 30-day mortality (ECOG 2 aOR= 7.99 (2.67–23.94, p<0.001), ECOG 3/4 aOR= 13.31 (4.04–43.89, p<0.001)). Conclusion: Functional status is independently associated with 30-day mortality after cancer surgery. Variation in outcomes across income levels may be influenced by inherent differences between surgical populations.